MAIN FORMS OF WORK ON DICTION IN THE PROCESS VOCAL AND CHORAL EDUCATION OF STUDENTS ON MUSIC LESSONS (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the questions of vocal-choral skills, The principles of vocal exercises’ selection, methods of working at vocal exercises are underlined. The article is addressed to the future music teachers.